The corporate director : new roles--new responsibilities : a report of the Corporate Directors Conference - Arthur D.Little, Inc.; New York Management Center (Boston : Cahners Books, 1975)
This study served a very useful purpose. It caused many people to be concerned about the finite character of the earth's resources and the alarming growth rate of the earth's population.
Includes bibliographical references.
hza 16/07/2018
Loans
Keywords: Directors of corporations; United States of America